Molecular Diagnosis and Genetic Variation of Termite Infest Palm Trees - Aqeel A. Qraidi; Muslim Ashor Al-etby; Aqeel Alyousuf; Ashraf A. Mohammed (مجلة ديالى للعلوم الزراعية)
A molecular diagnosis study was conducted on termite insect that invades palm trees. BLAST results showed that most of the samples were matched to the Microserotermes sp. with accession number KY224717.1, except one sample matched with Amitermes desertorum and Amitermes vilis with accession number KU523914.1, KU523912.1, respectively which is Garma-2 with query cover reaching 95.73% , 95.445 respectively. The results of the similarity and likelihood algorithm analysis showed the emergence of two main clusters, the first cluster includes taxa samples of the Microcerotermes diversus species with a taxa from the National Gene Bank (KY224717.1) for comparison, the second cluster includes the taxa from Gurma-2 region, which was morphologically classified as Amitermes vilis, with the comparison taxa from the National Gene Bank (KU523914.1) as out group (O.G) with a divergence branch length 0.06357. In general, the sequences of the cytochrome c oxidase (COXII) gene of the studied samples matched the sequences of the standard recorded samples in US GenBank with a matching rate of more than 97%, but some samples in phylogenetic tree showed a difference, as they gave a subcluster, which is an indicator of the development of a new subspecies or another species in the future perhaps.